2009
DOI: 10.4323/rjlm.2009.199
|View full text |Cite
|
Sign up to set email alerts
|

Atypical methods of suicide - case reports and literature review

Abstract: Suicide is an increasing public health problem all around the globe, because of the loss of lives with devastating effects on those left behind. The literature review shows that there are a lot of risk factors associated with suicide, but the psychiatric pathology or psychiatric imbalance at a certain critical moment in the individual's life seems to play a major role. This article presents four suicide cases autopsied at the National Institute of Legal Medicine-Bucharest in which the common characteristic is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Previous reviews revealed that approximately 90% of suicide victims were found to have had at least one axis 1 psychiatric comorbidity (3, 5, 9). Though more severe psychiatric morbidities are supposed to be present among the individuals who have died by unusual methods, this review finding does not support such notion (28). Seven (28%) victims had notable risk factors such as financial burdens (2), personality domains (2), marital and family discord (2), and imprisonment (1).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous reviews revealed that approximately 90% of suicide victims were found to have had at least one axis 1 psychiatric comorbidity (3, 5, 9). Though more severe psychiatric morbidities are supposed to be present among the individuals who have died by unusual methods, this review finding does not support such notion (28). Seven (28%) victims had notable risk factors such as financial burdens (2), personality domains (2), marital and family discord (2), and imprisonment (1).…”
Section: Discussionmentioning
confidence: 78%
“…Suicide by violent head impalement was found in an 80-year-old man with pancreatic cancer and depression (22). Salem et al (28), reported in Romania the suicide of a 76-year-old male who drilled his own chest using a drill borer. When two or more methods are applied either simultaneously or one after another in a suicide, it is called complex suicide (11,14,33).…”
Section: Suicide By Violent Methodsmentioning
confidence: 99%
See 1 more Smart Citation